2006
DOI: 10.1002/art.22280
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence of a cytokine and chemokine network in three patients with Erdheim‐Chester disease: Implications for pathogenesis

Abstract: Objective. Erdheim-Chester disease (ECD) is a rare form of non-Langerhans' cell histiocytosis (LCH) of unknown etiology, characterized by diffuse histiocyte infiltration of bones and soft tissue. The purpose of this study was to assess cell proliferation and expression of cytokines, chemokines, and chemokine receptors that may potentially be important in histiocyte accumulation in ECD lesions.Methods. Biopsies were performed on 3 patients with ECD. The diagnosis of the disease was based on clinical signs inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 14 publications
3
79
1
3
Order By: Relevance
“…These cytokines released by the foamy macrophages can stimulate osteoclast activity, and bisphosphonate can play a role in inhibiting the activity. In addition to these cytokines, receptor activator of NF-kappaB ligand (RANKL) was reported to be expressed in the foamy macrophages of bone lesion (53%) and lung (15%) [31]. If this is the case, administration of anti-RANKL antibody might be a therapeutic option in our patient, by targeting not only to osteoclast references…”
Section: Appendixmentioning
confidence: 82%
See 1 more Smart Citation
“…These cytokines released by the foamy macrophages can stimulate osteoclast activity, and bisphosphonate can play a role in inhibiting the activity. In addition to these cytokines, receptor activator of NF-kappaB ligand (RANKL) was reported to be expressed in the foamy macrophages of bone lesion (53%) and lung (15%) [31]. If this is the case, administration of anti-RANKL antibody might be a therapeutic option in our patient, by targeting not only to osteoclast references…”
Section: Appendixmentioning
confidence: 82%
“…Pro-inflammatory cytokines, such as interleukin-1α (IL-1α), tumor necrosis factor α (TNF-α) and IL-6, were reported to be strongly expressed in the foamy macrophages of ECD [31]. These cytokines released by the foamy macrophages can stimulate osteoclast activity, and bisphosphonate can play a role in inhibiting the activity.…”
Section: Appendixmentioning
confidence: 99%
“…In these diseases, FDG uptake is believed to be related to the high density of activated macrophages present in inflammatory lesions. While there is ongoing debate regarding the exact origin of the histiocytes in ECD (25,26), these cells are of the monocyte/ macrophage/dendritic cell lineages (27,28). This may account for the observed uptake in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Stoppacciaro et al reported an immunohistochemical study of three patients, revealing that a complex network of cytokines and chemokines regulates histiocyte recruitment and accumulation in the lesions [57]. Dagna et al studied both spontaneous and stimulated cytokine production by mononuclear cells in biopsy fragments from a single patient [58]: tumor necrosis factor α was produced after stimulation, and IL-6 and IL-8 were secreted spontaneously, with IL-8 acting as a chemoattractant for polymorphonuclear cells and monocytes.…”
Section: Pathophysiologymentioning
confidence: 99%